Bismuth nanomaterials as contrast agents for radiography and computed tomography imaging and their quality/safety considerations. (23rd November 2022) - Yu, Huan; Guo, Haoxiang; Wang, Yong; Wang, Yangyun; Zhang, Leshuai
Abstract: Contrast agents for radiography and computed tomography (CT) scans are substances that can enhance the contrast of blood vessels and soft tissue with detailed imaging information of the diseased sites. However, the large doses, short circulation time and adverse effects are the intrinsic limitations of CT contrast agents, preventing their extended and safe use in the clinical setting. Bismuth nanoparticles (NPs) have gained attention for the high X‐ray absorption of bismuth elements with acceptable biocompatibility, showing their potential to be translated into commercialized CT contrast agents. Compared with traditional iodine contrast agents, bismuth NPs are characterized by prolonged circulation time and enhanced contrast, largely due to the surface modification and enhanced permeability and retention effect of NPs. Bismuth NPs can also be flexibly upgraded into sophisticated nanoagents for multimodal imaging and therapeutic purposes by complexation with supporting chemicals, small molecule drugs, fluorescence labels, and other functional agents. Additionally, the affinity and retention of the bismuth NPs in the diseased sites can be further improved by modification of the targeting moiety on the NPs surface. However, a simple synthetic process and low complexity of bismuth NPs are highly recommended for scaling out and quality control of nanoagents with commercialization potential. Since product safety is a prerequisite for the translation of bismuth NPs from bench to the clinic, we focus on recent advances in the distribution, elimination, and toxicity of bismuth NPs previously reported. Finally, we delineate the associated mechanisms for nephrotoxicity and the strategy to reduce the toxicity of bismuth NPs. This article is categorized under: Diagnostic Tools > In Vivo Nanodiagnostics and Imaging Toxicology and Regulatory Issues in Nanomedicine > Toxicology of Nanomaterials Abstract : Schematic illustration of Bismuth‐based nanoparticles (Bi‐based NPs) the current research progress on the diagnostic imaging concerning their long circulation time, multimodal application, active targeting ability and the quality/safety concerns. CMA, critical material attributes; CPP, critical process parameters; CQA, critical quality attributes; DoE, design of experiment; DS, design space.